เพศศึกษา: เสียงสะท้อนจากวัยรุ่นไทย (Sex Education: Thai Adolescent’s Voices) - จิรวัฒน์กุล, ศิริพร; แสวงเจริญ, กฤตยา; จงอุดมการณ์, ดารุณี; กิตติวัฒนไพศาล, วราลักษณ์; รุ่งเรืองกลกิจ, สมพร; โคตนารา, อิงคฎา (วารสารพยาบาลศาสตร์และสุขภาพ, 2014)
Objective: To explore meaning and perception of sex education among adolescents. Method: Qualitative study was employed. Seven provinces including Kumpangphet, Nakornrachasima, Samtsakorn, Samutsongkarm, Prachoabkeereekun, Suratthanee and Narathiwat were chosen as study sites. Using purposive sampling, 451 boys and girls aged 9-19 who were in primary school, high school, vocational school and who dropped out from school were chosen. Focus group discussions and in-depth interviews were conducted. Data was analyzed using content analysis.  Results: Four main themes were found including 1) sex education is about sexual intercourse and birth control, 2) sex education can be learned from everywhere except at home and school, 3) parents and teachers need to open their mind and 4) openly discussion on sex education should be done. Conclusion: Findings reveal that reviewing and revolution of concepts and teaching methods on sex education are needed both at home and school.